Inhibition of tamoxifen’s therapeutic effects by emodin in estrogen receptor-positive breast cancer cell lines - Kim, Yun Gyoung; Park, Yoon Hwa; Yang, Eun Yoel; Park, Won Seo; Park, Kyoung Sik (Annals of surgical treatment and research, 2019)
This study was aimed to investigate the combination effect of endoxifen and emodin on estrogen receptor (ER) positive breast cancer cell lines and to explain the mechanism of the combination effect. We conducted this study on MCF-7 (ER+/human epidermal growth factor receptor-2 [HER2]-), T47D (ER+/HER2-), ZR-75-1 (ER+/HER2+), and BT474 (ER+/HER2+) cell lines, which confirmed combination effect of endoxifen and emodin. Optimal concentrations for combination were determined to study the effects on proliferation of MCF-7 and ZR-75-1 cells. Analysis of the combination effect was carried out in the CompuSyn software. The combination of downstream mechanisms, and combined effects of other similar compounds were tested on the MCF-7 and ZR 75-1 cell lines. Protein expression was confirmed by western blot. The combination of endoxifen and emodin had antagonistic effects on MCF-7 and ZR-75-1cell lines (combination index > 1). We validated the antagonistic effect in T47D and BT474 cell lines. During the combined treatment, the results showed elevated amounts of cyclin D1 and phosphorylated extracellular signal-regulated kinase (pERK). Analysis of drug interactions showed antagonistic effect between endoxifen and chemical compounds similar to emodin, such as chrysophanol or rhein, in MCF-7 and ZR-75-1 cells. Addition of emodin attenuated tamoxifen's treatment effect via cyclin D1 and pERK up-regulation in ER-positive breast cancer cell lines.